The nexus of Sugar-Sweetened Beverages: Insights on demographics, enablers and barriers - Khamis Al-Alawy, MSc; Reem Gaafar, MBBS, MPH; Immanuel Azaad Moonesar, PhD, R.D; Shatha Muhsineh, MPH (Elsevier, 2021)
Objectives: The study objectives were to a) explore the association between household income and nationality and Sugar-Sweetened Beverage (SSB) enablers and barriers, and b) inform public health policy and health promotion. Study design: A Cross-sectional Study in the UAE. Methods: Nationally representative population survey was used to capture demographic and SSB behaviour data. Results: We recruited 7500 participants into the study and received 1290 responses (17.2% participation rate). We report statistically significant associations between household income, nationality, and enablers and barriers. In some instances, similar enablers and barriers were reported by household income and nationality. Conclusions: There are several associations between household income, nationality and SSB enablers, and barriers. These associations should be considered for future public health policy and health promotion decision-making to reduce SSB consumption. In addition, further research is needed to explore how other demographic factors (modifying variables) are associated with SSB enablers and barriers.